Analysis and Performance Evaluation of Electric Springs and STATCOM for Compensating Voltage Fluctuations (International Journal of Engineering and Computer Science, 2017)
The concept of electric spring (ES) has been proposed recently as an effective means of distributed voltage control. The idea is to regulate the voltage across the critical (C) loads while allowing the noncritical (NC) impedance-type loads (e.g., water heaters) to vary their power consumption and thus contribute to demandside response. In this paper, a comparison is made between distributed voltage control using ES against the traditional single point control with STATic Compensator (STATCOM). For a given range of supply voltage variation, the total reactive capacity required for each option to produce the desired voltage regulation at the point of connection is compared. A simple case study with a single ES and STATCOM is presented first to show that the ES and STATCOM require comparable reactive power to achieve similar voltage regulation. Comparison between a STATCOM and ES is further substantiated through similar case studies on the IEEE 13-bus test feeder system and also on a part of the distribution network in Sha Lo Wan Bay, Hong Kong. In both cases, it turns out that a group of ESs achieves better total voltage regulation than STATCOM with less overall reactive power capacity. Dependence of the ES capability on the proportion of critical and NC load is also shown